The Behavioral and Intermediate Effects of Advertising on Firm Performance: An Empirical Investigation of the Restaurant Industry. (February 2018) - Kim, Jewoo; Jun, Jinhyun; Tang, Liang (Rebecca); Zheng, Tianshu
The purpose of this study was to identify tangible and intangible gains resulting from advertising in restaurant businesses from both the marketing and finance/accounting perspectives. Specifically, this study examined both behavioral and intermediate effects of advertising on consumer behavior and firm performance. Annual sales, profit, Tobin's Q, and advertising expenditure of 119 restaurant firms from 1991 to 2012 were used for data analysis. The findings revealed that advertising led to an immediate increase in consumer demand, but failed to improve profit. The effect of advertising on sales and profit through brand equity was found to be insignificant. This study suggests a new angle on the use of advertising and brand strategies in the restaurant industry and discusses potential directions for future research.